2003
DOI: 10.1152/ajpheart.00214.2003
|View full text |Cite
|
Sign up to set email alerts
|

Renal vascular responses to static handgrip: role of muscle mechanoreflex

Abstract: During exercise, the sympathetic nervous system is activated, which causes vasoconstriction. The autonomic mechanisms responsible for this vasoconstriction vary based on the particular tissue being studied. Attempts to examine reflex control of the human renal circulation have been difficult because of technical limitations. In this report, the Doppler technique was used to examine renal flow velocity during four muscle contraction paradigms in conscious humans. Flow velocity was divided by mean arterial blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
112
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(124 citation statements)
references
References 39 publications
12
112
0
Order By: Relevance
“…The results of the present study indicate that, in humans, heating the forearm muscles elicits a similar influence on mechanoreceptor-mediated renal vasoconstriction, because the differences in renal vasoconstriction occurred only during exercise but not when the muscle metaboreceptors were engaged in isolation during postexercise muscle ischemia. These findings are in agreement with other studies that have found that mechanoreceptors contribute to decreases in renal conductance in humans (14,15) and decreases in renal conductance and sympathetic nerve activity in animals (9,10,29). The greater decrease in calf vascular conductance with heating corresponds to greater increases in muscle sympathetic nerve activity, which we observed previously using the same protocol (19).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of the present study indicate that, in humans, heating the forearm muscles elicits a similar influence on mechanoreceptor-mediated renal vasoconstriction, because the differences in renal vasoconstriction occurred only during exercise but not when the muscle metaboreceptors were engaged in isolation during postexercise muscle ischemia. These findings are in agreement with other studies that have found that mechanoreceptors contribute to decreases in renal conductance in humans (14,15) and decreases in renal conductance and sympathetic nerve activity in animals (9,10,29). The greater decrease in calf vascular conductance with heating corresponds to greater increases in muscle sympathetic nerve activity, which we observed previously using the same protocol (19).…”
Section: Discussionsupporting
confidence: 93%
“…During exercise, renal vasoconstriction appears to be mediated by activation of the exercise pressor reflex (4,15,29). This reflex is controlled by mechanically and metabolically sensitive afferents in the working muscle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid sympathetic nerve responses are hardly explained by the muscle mechanoreflex. Momen et al (31,32) recently reported that a 15-s bout of evoked static muscle contraction by percutaneous electrical stimulation increased renal vascular resistance in humans, suggesting that muscle mechanoreflex engagement was responsible for the increase in renal vascular resistance. Taken together, the muscle mechanoreflex may not work on the whole vascular system but may affect the renal vascular bed particularly.…”
Section: Central Command But Not the Muscle Mechanoreflex Is Responmentioning
confidence: 99%
“…Immediately before exercise was stopped, posthandgrip circulatory arrest (PHG-CA) was initiated by inflation of a previously placed BP cuff around the arm at ϳ250 mmHg, which was kept inflated for 2 min. Vascular resistance responses during PHG-CA are thought to be due to 1) engagement of the muscle metaboreflex; and/or 2) myogenic vasoconstriction, if BP remains above baseline (13).…”
Section: Study Protocolsmentioning
confidence: 99%